2020
DOI: 10.1002/slct.202003959
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Docking and Antihypertensive Activity of Pyridone Derivatives

Abstract: A substituted 4-((5-cyano-1-ethyl-2-hydroxy-4-methyl-6-oxo-1,6-dihydropyridin-3-yl)diazenyl)benzene-sulfonamides were picked up via coupling of aromatic Diazonium salt for sulfonamide derivatives on 3-cyano-6-hydroxyl-2-pyridone derivative. The synthesized 4-((pyridinyl)azo)benzene-sulfonamide analogues have been evidenced through elemental and spectral analyses "FT-IR, 1 HNMR, 13 CNMR and MS". The produced derivatives were exposed to molecular docking to predict their antihypertensive activity toward protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
1
7
0
4
Order By: Relevance
“…Here, positive values indicate stronger bond strength between the ligands and the receptor's binding pocket. Despite the positive values, the binding energy range aligns with previous studies investigating the potential of compounds as antihypertensive drugs based on binding energy values [4,12,13]. These studies used different ligands and receptors, but their results demonstrated similar value ranges for binding energy, indicating their activity as potential antihypertensive agents.…”
Section: Molecular Dockingsupporting
confidence: 83%
See 2 more Smart Citations
“…Here, positive values indicate stronger bond strength between the ligands and the receptor's binding pocket. Despite the positive values, the binding energy range aligns with previous studies investigating the potential of compounds as antihypertensive drugs based on binding energy values [4,12,13]. These studies used different ligands and receptors, but their results demonstrated similar value ranges for binding energy, indicating their activity as potential antihypertensive agents.…”
Section: Molecular Dockingsupporting
confidence: 83%
“…In addition to combination therapies, the development of antihypertensive drugs can also involve the synthesis of derivative compounds. For instance, Masaret et al [12] successfully developed antihypertensive drug compounds by synthesizing pyridone derivatives. Furthermore, there have been advancements in the development of antihypertensive drug compounds through synthesis and molecular docking methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature survey has reported that many pyridine derivatives play a vital role in vasorelaxation therapeutics. 15 For example, milrinone and amrinone are positive inotropic agents with vasodilator properties; nifedipine is a peripheral and coronary vasodilator drug of the calcium channel blockers. [15][16][17] Furthermore, different pyridine-3-carbonitrile analogs I, II and different nicotinate esters such as micinicate, hepronicate and inositol nicotinate have emerged as signicant vasodilating agents (Fig.…”
Section: Numerous Antihypertensive Candidates Have Been Developedmentioning
confidence: 99%
“…N-heterocycles and linear products synthesized from sulfonamides or containing a sulfonamide fragment in the side chain are important objects for studying biological activity. Traditionally, sulfonamides are primarily considered as antibacterial agents; however, among these substances one can find not only effective antibiotics [1,2], but also compounds with very different activities: oral hypoglycemic [3,4], antitumor [3,5], antiviral [6][7][8][9], antiepileptic [10], antihypertensive [11], antiprotozoal [12], antifungal [13], anticancer [14][15][16], anti-inflammatory [17], diuretic [18], butyrylcholinesterase inhibitors (anti-Alzheimer's disease activity) [19], MAO-B specific inhibitors (activity in the treatment of neurodegenerative disorders such as Parkinson's disease) [20], COX-2 inhibitors (therapy of inflammatory disease) [21], etc. Recent advances in the medicinal chemistry of sulfonamides showed the possibilities of new unique drug design.…”
Section: Introductionmentioning
confidence: 99%